Power systems control and reliability : electric power design and enhancement - Qamber, Isa S. (Apple Academic Press, 2020)
"This new volume, Power Systems Control and Reliability: Electric Power Design and Enhancement, focuses on power systems reliability and generating unit commitments. These reliability techniques are essential in the design and evaluation of the electric power systems for planning, control, and operation. This informative volume covers the concepts of basic reliability engineering, such as power system spinning reserve, types of load curves and their objectives and benefits, the electric power exchange, and the system operation constraints. The author explains how the probability theory plays an important role in reliability applications and discusses the probability applications in electric power systems that led to the development of the mathematical models that are illustrated in the book. The algorithms that are presented throughout the chapters will help researchers and engineers to implement their own suitable programs where needed and will also be valuable for students. The Artificial Neural Networks (ANN) and Fuzzy Logic (FL) systems are discussed, and a number of load estimation models are built for some cases, where their formulas are developed. A number of developed models are presented in the book, including the Kronecker techniques, Fourth-Order Runge-Kutta, System Multiplication Method, or Adams Method; and components with different connections and different distributions are presented. A number of examples are explained showing how to build and evaluate power plants. The volume goes on to discuss the equivalent transition rate matrix and using the Laplace Transforms technique to calculate the transient probabilities. Finally, a comparison between different states models compared. This valuable volume, providing a comprehensive overview of power systems operation and the power systems reliability, will be helpful to engineers, researchers, faculty, and students in electric power systems control and design."--